THE METHODOLOGY OF USING PISA TESTS IN TEACHING PHYSICS IN SECONDARY SCHOOLS IN PHYSICS - Ochilova Ozoda Odilovna; Karimova Nozliya Nabijon qizi; Absalyamova Ilmira Ildarovna; Abdullayeva Shoira Isajanovna (PEDAGOGS, 2024)
Annotation: This article explores the methodology of integrating PISA (Programme for International Student Assessment) tests in the teaching of physics in secondary schools. The PISA test, which evaluates 15-year-olds in reading, mathematics, and science, provides a comprehensive tool for enhancing students’ analytical and problem-solving skills in physics. By aligning teaching methods with the cognitive framework of PISA, educators can promote a deeper understanding of core physics concepts. The study presents a framework for incorporating PISA tasks into lessons, evaluates the effectiveness of this approach, and offers suggestions for educators.